Peningkatan Kreativitas Mahasiswa Melalui Inovasi Produk Gantungan Kunci Foto Akrilik sebagai Media Ekspresi Diri dan Nilai Ekonomis - Guruh Larasti; Anggit Dyah Kusumastuti (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Creativity and innovation are essential elements in developing student competencies, especially in the Business Administration study program. This community service activity aims to enhance students’ creativity through training in producing an innovative product, namely gantungan kunci foto akriliks, which serve as a medium for self-expression and possess economic value. The activity was conducted for the 2023 cohort of Business Administration students at Universitas Sahid Surakarta using methods including counseling, technical training, and hands-on practice. The results show that students were able to create creative and unique designs while understanding the concept of market value through personalized products. In addition to improving design and production skills, this activity also fosters entrepreneurial spirit and awareness of business potential based on creativity. This training is expected to equip students to continuously develop innovative ideas that can be implemented in the business world